DEVELOPMENT OF VALUE AND SENSE CONSCIOUSNESS OF JUNIOR SCHOOLCHILDREN IN MATHEMATICS LESSONS - N.D. Mayborodyuk (Academy of Cognitive and Natural Sciences, 2010)
In the articles demonstration experimental material of pedagogical model of the personality oriented lesson opens up on development of valuable-semantic consciousness ofpupils ofprimary classes on the lessons of mathematics.